An Open‐Ended Ni3S2–Co9S8 Heterostructures Nanocage Anode with Enhanced Reaction Kinetics for Superior Potassium‐Ion Batteries. Issue 18 (28th March 2022) - Zhang, Shipeng; Ling, Fangxin; Wang, Lifeng; Xu, Rui; Ma, Mingze; Cheng, Xiaolong; Bai, Ruilin; Shao, Yu; Huang, Huijuan; Li, Dongjun; Jiang, Yu; Rui, Xianhong; et al.
Abstract: Sulfides are perceived as promising anode materials for potassium‐ion batteries (PIBs) due to their high theoretical specific capacity and structural diversity. Nonetheless, the poor structural stability and sluggish kinetics of sulfides lead to unsatisfactory electrochemical performance. Herein, Ni3 S2 –Co9 S8 heterostructures with an open‐ended nanocage structure wrapped by reduced graphene oxide (Ni‐Co‐S@rGO cages) are well designed as the anode for PIBs via a selective etching and one‐step sulfuration approach. The hollow Ni‐Co‐S@rGO nanocages, with large surface area, abundant heterointerfaces, and unique open‐ended nanocage structure, can reduce the K + diffusion length and promote reaction kinetics. When used as the anode for PIBs, the Ni‐Co‐S@rGO exhibits high reversible capacity and low capacity degradation (0.0089% per cycle over 2000 cycles at 10 A g –1 ). A potassium‐ion full battery with a Ni‐Co‐S@rGO anode and Prussian blue cathode can display a superior reversible capacity of 400 mAh g –1 after 300 cycles at 2 A g –1 . The unique structural advantages and electrochemical reaction mechanisms of the Ni‐Co‐S@rGO are revealed by finite‐element‐simulation in situ characterizations. The universal synthesis technology of bimetallic sulfide anodes for advanced PIBs may provide vital guidance to design high‐performance energy‐storage materials. Abstract : Ni3 S2 –Co9 S8 heterostructures with an open‐ended nanocage structure wrapped by reduced graphene oxide (Ni‐Co‐S@rGO cages) are accurately designed and synthesized by a selective etching and one‐step sulfuration method, which displays excellent electrochemical performance as the anode for potassium‐ion batteries.